Analysis of the Influence of Social Media Marketing in Increasing Brand Awareness and Customer Engagement on Purchasing Decisions in the Coffee Shop Industry in Denpasar - I Gusti Ayu Nia Antari; Gde Bayu Surya Parwita; Ni Putu Nita Anggraini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of social media marketing in increasing brand awareness and customer engagement on purchasing decisions in the coffee shop industry in Denpasar City. The development of social media has encouraged business actors to adopt digital marketing strategies to maintain competitiveness, especially in the coffee shop industry which is experiencing rapid growth. This study uses a quantitative approach with a survey method, involving 385 respondents selected through purposive sampling techniques. Data analysis was carried out using multiple linear regression methods and mediation analysis. The results of the study indicate that social media marketing has a positive and significant effect on brand awareness, customer engagement, and purchasing decisions. In addition, brand awareness and customer engagement have been shown to play a mediating role in the relationship between social media marketing and purchasing decisions. Thus, marketing strategies through social media can be an effective tool in increasing brand awareness, and customer engagement, and driving purchasing decisions in the coffee shop industry. These findings provide practical implications for business actors in designing more effective digital marketing strategies to increase competitiveness in the market.